Perception, satisfaction and feedback among employees in certified organisations on occupational safety and health management system in the Klang Valley, Malaysia - Awang, Noorhasimah (2019)
Occupational safety and health management is an important aspect especially for activities that are involved in working at a high risk workplace. The main cause of various issues in the industrial sector is due to the absence or lack of an efficient management system. Malaysia currently uses the Malaysian Standard (MS) 1722:2011 and Occupational Health and Safety Assessment Series (OHSAS) 18001: 2007. The aims of this study are to determine the perception, safety satisfaction and safety feedback of the Occupational Safety and Health (OSH) Management System among employees in certified organisations in the Klang Valley. A cross-sectional study using selfadministered questionnaires was conducted with a total of 300 respondents among 63 OSHMS certified organisations in the Klang Valley. The questionnaires consisted of four sections: socio-demographic, employee perception, safety satisfaction and safety feedback. IBM Statistical Package for Social Science (SPSS) was used to analyse all collected data. The findings revealed higher employee perception on OSHMS in evaluation (4.15 ± 0.56) and action for improvement (4.04 ± 0.53). Evaluation consisted of performance monitoring and measurement, incident investigation, audit and management review. The overall view of respondents towards the implementation of MS 1722 was positive which was in the moderate to good score. The findings revealed higher level of safety satisfaction of OSHMS in evaluation (3.77 ± 0.49) and action for improvement (3.68 ± 0.64). Employees’ overall job satisfaction towards the implementation of MS 1722 certification was also positive (moderate – good score). Based on the safety feedback finding, respondents agreed that allowance or incentive from employers will encourage them to take safety as an important issue. Findings on the relationship between certified organisation and satisfaction show that only evaluation (r= - 0.134, p= 0.020) was significant since the p-value was smaller than 0.05. It is recommended that organisations should proceed to be certified in OSHMS for safety culture. Employee perception, satisfaction, and feedback, on the other hand, would be an important indicator to measure the effectiveness of OSH Management System implemented in the organisation as well as creating a positive safety culture. As a conclusion, further study can be extended about the need for OSHMS to ensure continuous OSH performance improvement and reduce accidents or occupational diseases.